The Determinants of Behavior of HIV Testing in Pregnant Mothers - Harahap, Meilani; Pulungan, Nikmatul Khoiriyah; Hasibuan, Ennysah (International Journal of Public Health Excellence (IJPHE), 2022)
HIV infection in Indonesia is one of the health problems and infectious diseases that can affect maternal and child mortality. More than 90% of HIV-infected infants are infected by HIV-positive mothers. Transmission can occur during pregnancy, during delivery and during breastfeeding. Early detection of HIV is important so that antiretroviral virus (ARV) drug therapy is carried out more quickly to reduce the rate of HIV transmission from mother to baby. The research, which was conducted at the Balongan Subdistrict Health Center, Indramayu Regency, was conducted to determine the determinants associated with HIV testing behavior during pregnancy. This type of research is quantitative with a cross-sectional study design using the total population. The results of the univariate analysis showed that 71.1% of mothers did not take an HIV test during pregnancy. and education about HIV/AIDS, because the husband is the closest person to the mother so that the husband makes a big contribution to providing support to the mother